Type of "multiple" narrator in the narrative structure of the artistic text - Кушнірова, Тетяна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The present article is concerned with the concept of "narrative" as a literary category, its characteristics and structural elements. In literary studies one can find a lot of scholarly works devoted to this problem, however there are still many questions that deserve further and more detailed consideration. The author of the article concretizes the idea of "narrative", analyzes the main narrative theories, compares the basic concepts of narratology in the scientific works of outstanding scholars. This is narrator’s projection and world-view, his/her view of life, the so-called glance at the world. The narrator may be different, he/she can take on different masks. Narrative components may be various in in each specific case, that is in every particular text. It depends on narration style and the peculiarities of the author’s myth. This article presents the types of narrator, in particular, the so-termed "multiple" type of the narrator (the assemblage of voices, the angle of "reality"), who sees and perceives the artistic world ambivalently. All the structural elements of such narrator’s type are endowed with individual features and have their own outlook. The "multiple" narrator can be found in the works of original genre with complex compositional and narrative structure. In such narrative structures, the narrator can create his own "reality", his own author’s myth through the view angle of each character. This is typical of modern genre forms, built on the new genre canons, such as novel forms of the "talk show" format or "sms" - novel. The "multiple" narrator forms the structure, provides plot-compositional unity, “leads” narrative story and influences the genre modification of the literary work. Structural types of "multiple" narrator can perceive the reality subjectively and have the ability to present their own vision of reality and interact with other narrative components: narratator, recipient, author-demiurge, the signs of which are closely interwoven in the modern text.